2015
DOI: 10.3164/jcbn.14-74
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cell wall components regulate adipokine secretion from visceral adipocytes

Abstract: Recent studies suggest a relationship between intestinal microbiota and metabolic syndromes; however, the underlying mechanism remains unclear. To clarify this issue, we assessed the effects of bacterial cell wall components on adiponectin, leptin and resistin secretion from rat visceral adipocytes in vitro. We also measured the relative population of Firmicutes and Bacteroidetes in fecal microbiota and the amount of fecal mucin as an intestinal barrier function, when mice were fed a high-fat diet. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…The present studies observed a strong correlation between the Faecalibacterium and serum adiponectin in MS patients. Studies suggest that gram positive cell wall components stimulate adiponectin production (Taira et al, 2015). Whether the presence of Faecalibacterium in the gut microbiome has a direct or indirect role in modulation of serum adiponectin warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The present studies observed a strong correlation between the Faecalibacterium and serum adiponectin in MS patients. Studies suggest that gram positive cell wall components stimulate adiponectin production (Taira et al, 2015). Whether the presence of Faecalibacterium in the gut microbiome has a direct or indirect role in modulation of serum adiponectin warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that LPS acts as a master switch to control adipose tissue metabolism both in vivo and ex vivo by blocking cannabinoiddriven adipogenesis [10]. Additionally, LPS inhibited the secretion of adipokines, specifically adiponectin, from the visceral adipose tissue [22], that may affect the onset of metabolic syndrome. Further, it has been reported that decreased production of N -acylethanolamines, an important mediators of metabolic homeostasis and inflammation, in the adipose tissue induced intestinal barrier dysfunction and dysbiosis of the gut microbiota, which in turn participates in the metabolic alterations observed in the adipose tissue [23].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding other TLRs implicated in NAFLD pathogenesis, TLR2 is also a cell surface receptor, which is involved in the recognition of a wide range of pathogen-associated molecular patterns (PAMPs) including peptidoglycan, a component of the cell surface of Gram-positive bacteria [ 75 ]. These subtypes of bacteria include Firmicutes, whose increase has been reported in animal models and humans subjected to a high-fat diet [ 99 ]. Furthermore, this dysbiosis has also been associated with NAFLD [ 100 ].…”
Section: Innate Immunity In Nonalcoholic Fatty Liver Disease: Rolementioning
confidence: 99%